Frequency of Attendance and Interaction of Students in 3D Multi-User Virtual Environments (MUVEs): The Effect on Learning English Language - Khan, Muhammad Saleem; Safaan, Samy Abdelwahab (Advances in Social Sciences Research Journal, 2017)
This research study of third-dimensional multi-users virtual environment is experienced at Buraydah community college, Qassim University by the Saudi EFL students of level three in their Computer Assisted Language Learning course. In this paper the personal presence of the participants and their frequency of interaction are investigated. The English language laboratory was used to provide 3D multi-users virtual environment to the participants by awarding each of them an avatar character of their own choice. These were designed to practice and improve the proposed speaking skills of English language as a foreign language. This environment provides the participants to concentrate on their speaking skills to improve it by collaboration, participation, and frequent interactions. The results from such multi-users virtual social interactions showed a positive academic success of the participants in the current study. In Saudi culture, the language students have least interaction for improving their spoken skills of English where a 3D multi-users interaction is recommended for success of spoken English.